2018
DOI: 10.3389/fnagi.2017.00437
|View full text |Cite
|
Sign up to set email alerts
|

Declines in Connected Language Are Associated with Very Early Mild Cognitive Impairment: Results from the Wisconsin Registry for Alzheimer’s Prevention

Abstract: Changes to everyday spoken language (“connected language”) are evident in persons with AD dementia, yet little is known about when these changes are first detectable on the continuum of cognitive decline. The aim of this study was to determine if participants with very early, subclinical memory declines were also showing declines in connected language. We analyzed connected language samples obtained from a simple picture description task at two time points in 264 participants from the Wisconsin Registry for Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
71
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 74 publications
10
71
0
1
Order By: Relevance
“…Despite the lack of significant group differences on individual measures, the complete model showed a discriminative function and was able to distinguish MCI from SCI and MCI from HC, but not SCI from HC. Other studies have reported similar results (Ahmed et al, 2013;Mueller et al, 2018Mueller et al, , 2016Roark et al, 2011).…”
Section: Introductionsupporting
confidence: 72%
“…Despite the lack of significant group differences on individual measures, the complete model showed a discriminative function and was able to distinguish MCI from SCI and MCI from HC, but not SCI from HC. Other studies have reported similar results (Ahmed et al, 2013;Mueller et al, 2018Mueller et al, , 2016Roark et al, 2011).…”
Section: Introductionsupporting
confidence: 72%
“…The findings of Snowdon and colleagues stimulated interest in the relation of language performance to onset of dementia-producing diseases, and the literature contains many reports of language performance deficits in individuals with confirmed MCI (Asgari, Kaye, & Dodge, 2017;Bertola et al, 2014;Cardoso, Silva, Maroco, Mendonça, & Guerreiro, 2014;Choi, Kim, Lee, & Kim, 2013;Costa et al, 2014;Kim, Sung, & Jeong, 2012;Mueller et al, 2018Mueller et al, , 2015Nutter-Upham et al, 2008;Payne & Stine-Morrow, 2016;Smolik et al, 2016;Tsantali et al, 2013;Vaughan, Coen, Kenny, & Lawlor, 2016;Weakley, Schmitter-Edgecombe, & Anderson, 2013) and those with clinically diagnosed dementia (Bayles, McCullough, & Tomoeda, 2018;Bayles, Tomoeda, & Trosset, 1992;Tomoeda, Bayles, Trosset, Azuma, & McGeagh, 1996). The most commonly reported language performance deficit in individuals with MCI is impaired verbal fluency as measured by having individuals name as many items as possible in a category (Albert et al, 2011;Clark et al, 2013;Irish et al, 2011;Malek-Ahmadi, Raj, & Small, 2011;Tsantali et al, 2013;Weakley et al, 2013).…”
Section: And Language Impairmentmentioning
confidence: 99%
“…The rationale for this hypothesis was based on reports of very early changes in language abilities, even decades before other clinical symptoms appear (Mueller et al, 2018;Ohm et al, 1995;Snowdon et al, 1996;Tsantali et al, 2013) and the fact that successful completion of language tasks requires integrity of myriad cognitive operations as well as language knowledge and processing (Dell & O'Seaghdha, 1992;Fleming, 2014;Kirova et al, 2015;MacDonald & Christiansen, 2002;Malek-Ahmadi et al, 2011;Martin & Gupta, 2004;Oulhaj et al, 2009). Of the 14 ABCD subtests, the four that elicited the poorest performance were, in order, Repetition, Following Commands, Concept Definition, and Object Description.…”
Section: Hypothesis 2: Language Performance Tests Will Present a Greamentioning
confidence: 99%
See 1 more Smart Citation
“…Mueller et al [29] have documented spoken language as a noninvasive, multidimensional, and informative biological sample for the early diagnosis of AD, primary progressive aphasia, and other cognitive disorders. They also confirmed that connected language analysis is one of the most promising state-of-the-art diagnostic tools for MCI.…”
Section: Genetic Typesmentioning
confidence: 99%